2017
DOI: 10.3389/fmars.2017.00351
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Aquatic Observations through Recreation

Abstract: Accurate observations of the Earth system are required to understand how our planet is changing and to help manage its resources. The aquatic environment-including lakes, rivers, wetlands, estuaries, coastal and open oceans-is a fundamental component of the Earth system controlling key physical, biological, and chemical processes that allow life to flourish. Yet, this environment is critically undersampled in both time and space. New and cost-effective sampling solutions are urgently needed. Here, we highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…Here, we have demonstrated the value of using loggers deployed and maintained in shallow subtidal habitats, which allowed for a high number of match-ups with satellite-derived SST. Integrating these observations with other developing in situ techniques, such as citizen science [30][31][32][33]35], the tagging of marine vertebrates with sensors [71], coastal gliders [72] and autonomous beach buoy systems [73,74], may significantly enhance the spatial and temporal sampling of in situ data in the nearshore, and improve operational satellite SST retrievals.…”
Section: Forward Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have demonstrated the value of using loggers deployed and maintained in shallow subtidal habitats, which allowed for a high number of match-ups with satellite-derived SST. Integrating these observations with other developing in situ techniques, such as citizen science [30][31][32][33]35], the tagging of marine vertebrates with sensors [71], coastal gliders [72] and autonomous beach buoy systems [73,74], may significantly enhance the spatial and temporal sampling of in situ data in the nearshore, and improve operational satellite SST retrievals.…”
Section: Forward Outlookmentioning
confidence: 99%
“…They found a significant reduction in the performance of AVHRR algorithms at retrieving SST at the coastline, with root mean square differences over twice that observed from validations using buoy data a few kilometres offshore. Although there is remarkable potential for using surfers and other watersports participants for improving data collection in the nearshore coastal ocean [31][32][33][34][35], currently such datasets are relatively sparse and limited to conditions preferable for the activity, such that the findings of Brewin et al [30] were based on a relatively limited number of satellite and in situ match-ups.…”
Section: Introductionmentioning
confidence: 99%
“…Recreational fisheries are providing an increasing amount of data for researchers about their activity (e.g., Lloret et al, 2008;Giovos et al, 2018), but also about the ecosystems within they operate (e.g., Tiralongo et al, 2019), but the use of their FEK has been limited (see review by Hind, 2014). Given that there are many more recreational than commercial fishers (Hyder et al, 2018;Arlinghaus et al, 2019a), recreational fishers represent a relatively untapped source of long-term information on marine ecosystems (Brewin et al, 2017). Recreational FEK has been used to quantify variations in abundances and distribution of different fish stocks (e.g., Azzurro et al, 2011;Zukowski et al, 2011;Beaudreau and Levin, 2014;Sbragaglia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One solution gaining momentum is the integration of miniaturised environmental sensors into watersports equipment. New evidence has suggested that environmental monitoring in the nearshore could be drastically improved by harnessing vast numbers of citizens who partake in marine recreational sports [19]. To date, there have been studies looking at the use of divers [20][21][22], fishermen [23], stand-up paddle boarders [24], kayakers [25], sailors [26], and surfers [27,28].…”
Section: Introductionmentioning
confidence: 99%